2020
DOI: 10.1093/schbul/sbz140
|View full text |Cite
|
Sign up to set email alerts
|

Main Symptomatic Treatment Targets in Suspected and Early Psychosis: New Insights From Network Analysis

Abstract: Abstract The early detection and intervention in psychoses prior to their first episode are presently based on the symptomatic ultra-high-risk and the basic symptom criteria. Current models of symptom development assume that basic symptoms develop first, followed by attenuated and, finally, frank psychotic symptoms, though interrelations of these symptoms are yet unknown. Therefore, we studied for the first time their interrelations using a network approach in 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 73 publications
3
35
1
Order By: Relevance
“…Alternatively, the increase of CSA might be caused by cortical reorganization: Taking into consideration that UHR-symptoms are thought to develop from basic symptoms 63 or eventually arise in response to them, and the majority of UHR subjects in our sample also presents basic symptoms, the increased CSA might reflect these compensational processes, also discussed as indicator of resilience 60 . Yet, CSA increases did not correlate with symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the increase of CSA might be caused by cortical reorganization: Taking into consideration that UHR-symptoms are thought to develop from basic symptoms 63 or eventually arise in response to them, and the majority of UHR subjects in our sample also presents basic symptoms, the increased CSA might reflect these compensational processes, also discussed as indicator of resilience 60 . Yet, CSA increases did not correlate with symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, social anhedonia played a central role in mediating the relationship between positive and negative schizotypal personality traits ( Christensen et al, 2018 ). In health-seeking individuals, network analysis revealed that prodromal symptoms mediated the relationship between basic symptoms and frank symptoms of psychosis, with disorganized communication again playing a particularly central role ( Jimeno et al, 2020 ). Finally, by using network analysis, studies have shown that clinical manifestations that are not necessarily specific to psychosis, including in particular affective dysregulation, may play a prominent role in influencing the presence of psychotic-like experiences, in adolescence ( Fonseca-Pedrero et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…DCNA is a data mining method based on presenting variables as nodes (translated as gene expression in genetics) and pairwise correlations between them as links in the network. Due to the versatility of this method and its utility for visualizing and recognizing patterns in complex systems, it has been exported to several different areas apart from genetics, such as psychiatry 82 , neuroscience 83 or plant ecology 84 .…”
Section: Methodsmentioning
confidence: 99%